Az Európai Unió kohéziós politikája a kulturális örökségvédelem, és hagyományápolás terén Közép-Kelet Európában - Horváth, Péter (Közép-Európai Közlemények, 2015)
Within the EU cultural variegation is one of the most basic principles, thus member states have multiple ways to preserv their cultural heritage. On the other hand, one of the greatest challenge might be creating cooperation and coexistence of the members without undermining the culture and folklore of the individual nations. Cultural diversity will be accepted only if we are able- and willing to familiarize ourselves with it, by that we may get to know, or even embrace different cultural segments. The other important question is, what makes a tradition last and survive, because its alteration may result in maladaptation, which would likely be rejected by subcultures, as well as the majority.In our globalized and multicultural world, only our built and intellectual culture is able to help us to find our true selves.